Survival Rate of High-Rise Syndrome Cases Using Animal Trauma Triage Score in Cats - İnal, Kamil Serdar; Önyay, Taylan; Ersoy, Birsen Deniz Özbakır; Göl, Melis; Kurban, Elif Bağatır; Özak, Ahmet; Yardımcı, Cenk; Nisbet, Hatice Özlem; Sağlam, Kamil (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective To assess the data of high-rise syndrome (HRS) cases and determine the relationship between Animal Trauma Triage Score (ATTS), height, injury profile, and survival rate of patients.Study Design Retrospective study evaluating cats with HRS within a 4-year period.Results A logistic regression analysis which included height, ground type, and ATTS variables was performed to predict survival rate of patients. Only ATTS was significant among these variables (p < 0.001) and each point increase in ATTS increased the nonsurvival by 0.46 times (95% confidence interval [CI]: 0.347–0.624). The receiver operating curve indicates that ATTS is good at predicting mortality (area under the curve: 0.857; 95% CI: 0.788–0.926; p < 0.001).Conclusion The height of the fall, injury type, or ground type do not seem to be accurate in estimating the survival rate in HRS patients. Established scoring systems such as ATTS should be used to determine survival rates in future HRS studies.
Keywords: cats; fall; high-rise syndrome; Animal Trauma Triage Score; survival